Fat adaptation in well-trained athletes: effects on cell metabolism - Yeo, W. K.; Carey, A. L.; Burke, L.; Spriet, L. L.; Hawley, J. A. (Applied Physiology, Nutrition, and Metabolism, 2011)
The performance of prolonged (>90 min), continuous, endurance exercise is limited by endogenous carbohydrate (CHO) stores. Accordingly, for many decades, sports nutritionists and exercise physiologists have proposed a number of diet-training strategies that have the potential to increase fatty acid availability and rates of lipid oxidation and thereby attenuate the rate of glycogen utilization during exercise. Because the acute ingestion of exogenous substrates (primarily CHO) during exercise has little effect on the rates of muscle glycogenolysis, recent studies have focused on short-term (<1-2 weeks) diet-training interventions that increase endogenous substrate stores (i.e., muscle glycogen and lipids) and alter patterns of substrate utilization during exercise. One such strategy is "fat adaptation", an intervention in which well-trained endurance athletes consume a high-fat, low-CHO diet for up to 2 weeks while undertaking their normal training and then immediately follow this by CHO restoration (consuming a high-CHO diet and tapering for 1-3 days before a major endurance event). Compared with an isoenergetic CHO diet for the same intervention period, this "dietary periodization" protocol increases the rate of whole-body and muscle fat oxidation while attenuating the rate of muscle glycogenolysis during submaximal exercise. Of note is that these metabolic perturbations favouring the oxidation of fat persist even in the face of restored endogenous CHO stores and increased exogenous CHO availability. Here we review the current knowledge of some of the potential mechanisms by which skeletal muscle sustains high rates of fat oxidation in the face of high exogenous and endogenous CHO availability.